The Development of Interactive Learning Media on Android Platform Assisted By Google Sites - Afifah Afifah; Sabar Nurohman; Allesius Maryanto (Journal of Science Education Research, 2021)
This study aims to (1) produce interactive learning media on the android platform assisted by Google Sites that is feasible for junior high school Science learning of respiratory system, (2) produce media that is practical for junior high school Science learning of respiratory system. This development research employed 4D model (Define, Design, Development, and Dissemination). The subject of this research was the second semester of the eighth-grade students in Junior High School 1 Wonosari. Research instruments used in this research included validation sheets, practicality assessment sheets, and student response questionnaires. The results of this study indicate that (1) media is feasible with a percentage value in terms of material is 80% (feasible) and in terms of media is 87% (very feasible). (2) media are practically used with values of V in the aspect of material clarity of 0.86 with a very practical category, the aspect of clarity of display 0.80 with a practical category, the benefit aspect of 0.81 with a very practical category, the aspect of ease of use 0.79 with a practical category. The results from the students’ responses of media's practicality showed a P value of 79 %, included in the practical category.